Global initiatives for improving health and medication literacy - Mohd Taufek, Nor Hidayah (Elsevier, 2024)
Global initiatives in addressing health literacy have highlighted the specific measurement tools and action plans which are universal and applicable to various settings. These initiatives aim to reduce low health literacy levels through overcoming barriers and limitations in their implementation. The complexity of strategies, however, renders the interventions being applied primarily in resource constraint settings where health disparities are prominent. Conceptual frameworks have been utilized widely, but the evaluation of effectiveness of these initiatives requires regular monitoring and reporting by the responsible health authorities or agencies. The collaboration between multiple local stakeholders, and where possible, international organizations, is invaluable to improve the health outcomes in the population. Special attention needs to be focused on addressing low health and medication literacy in vulnerable groups and underserved communities. The health authorities globally have published and updated reliable sources and valid references for health and medication literacy initiatives to be adapted into local context. The impact of health and medication literacy initiatives were mixed, however, to a certain extent have improved health outcomes in some populations. The National Action Plan is one of the most impactful initiatives in implementing and reporting the effort at all levels, that involved the law guidance to ensure adherence to the evidence-based initiatives and outcome assessment. This chapter discusses key global initiatives for health and medication literacy.